2022
DOI: 10.1098/rspb.2022.1013
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional stress exacerbates impact of a novel insecticide on solitary bees' behaviour, reproduction and survival

Abstract: Pesticide exposure and food stress are major threats to bees, but their potential synergistic impacts under field-realistic conditions remain poorly understood and are not considered in current pesticide risk assessments. We conducted a semi-field experiment to examine the single and interactive effects of the novel insecticide flupyradifurone (FPF) and nutritional stress on fitness proxies in the solitary bee Osmia bicornis . Individually marked bees were released into flight cages wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 64 publications
0
16
0
Order By: Relevance
“…In the short term, regulators should restrict flupyradifurone use to non-flowering crops, while a re-assessment of its potential risk to pollinators can be re-evaluated. Ultimately, our results, and those that came before [14,55,[89][90][91][92], have demonstrated that pesticide risk assessments globally are failing to protect bees from the unintended consequences of pesticide use. Consequently, banning or restricting the use of certain agrochemicals (e.g.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…In the short term, regulators should restrict flupyradifurone use to non-flowering crops, while a re-assessment of its potential risk to pollinators can be re-evaluated. Ultimately, our results, and those that came before [14,55,[89][90][91][92], have demonstrated that pesticide risk assessments globally are failing to protect bees from the unintended consequences of pesticide use. Consequently, banning or restricting the use of certain agrochemicals (e.g.…”
Section: Discussionmentioning
confidence: 77%
“…Wild bee declines are driven by a multitude of different anthropogenic stressors, including pesticide use, and loss of habitat, as a consequence of intensive agriculture [7,[10][11][12]. Pesticide use can have both lethal [13,14] and sub-lethal [15][16][17][18][19] impacts on bees at field-realistic levels, which can influence bee populations [10,11]. Loss of habitat reduces floral resources which can impair bee nutrition [20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of our experimental design, we did not include colony parameters such as colony size, survival or production of reproductives; however, data concerning these traits are available in the literature for various bee species (e.g. [43][44][45][46][47][48][49], or reviewed in [89]).…”
Section: (C) Stress Affects Individual-level and Colony-level Develop...mentioning
confidence: 99%
“…Although other stressors such as nutritional stress are usually excluded, bees are challenged by a plethora of stressors in the field and, thus, investigations on a single stressor may not represent real-world field situations. Indeed, recent studies using laboratory and semi-field set-ups have demonstrated that the combined effects of nutritional stress and insecticides exacerbate each other, while high-quality diet buffers and mitigates the effects of insecticides in honeybees [43,44], bumblebees [45][46][47] and solitary bees [48,49].…”
Section: Introductionmentioning
confidence: 99%